Stereoselective synthesis of d-galactal-derived N-ethoxycarbonyl aziridine, as a new, improved synthetic protocol to glycal-derived N-activated vinyl aziridines. Issue 7 (16th February 2017) - Princiotto, Salvatore; Di Bussolo, Valeria; Bordoni, Vittorio; Favero, Lucilla; Crotti, Stefano; Uccello Barretta, Gloria; Balzano, Federica; Crotti, Paolo
Abstract: A new protocol for the synthesis ofd -galactal-derived N -ethoxycarbonyl vinyl aziridine1β-CO 2 Et, starting from tri- O -acetyl-d -glucal, is described. The new protocol constitutes a simple and fast access, with a satisfactory overall yield (5 steps, 36%), to ad -galactal-derived vinyl aziridine with a clear improvement compared with the previously described procedure leading to the structurally related N -nosyl aziridine1β-Ns which, starting from the same precursor, proceeded through 13 steps with a low, decidedly unsatisfactory, overall yield (3%). Graphical abstract: